The use of heterocyclic-based azo compounds bearing pyrrolidine, imidazole, triazole, and thiazole moieties for the treatment of neglected tropical disease caused by Schistosoma mansoni - Cauê Benito Scarim; Chung Man Chin (Elsevier, 2021)
Schistosomiasis (e.g. Schistosoma mansoni) is a neglected tropical disease caused by parasitic worms. It can advance from an acute (juvenile form) to chronic stage (adult form). Single-dose praziquantel (PZQ) is the only therapeutic drug option for adult schistosomiasis (SM) treatment, while its inability to efficiently inhibit earlier larval stages. Its use does not eliminate risks regarding the formation of resistant worms. Thus, new drug candidates to treat SM are urgently needed. Acting as molecule scaffolds, heterocyclic-based azo compounds have shown potential in the treatment of various diseases, including SM. This review article examines several medicinal chemistry-related studies involving these pharmacophore classes (pyrrolidine, imidazole, triazole, and thiazole) from 2011 to 2021, with a focus on SM. Our aim is to facilitate the drug design of novel molecules by optimizing anthelmintic conjugates.